A escola de quem não tem escola : os desafios da escolarização para jovens em situação de rua - Godinho, Josiane Machado (2015)
This study aims to understand the meaning of schooling for the young on the streets at the Porto Alegre Municipal School, maintained by the city of Porto Alegre/RS, in which are met, in addition to these young people, residents of the shelters and of communities away from the downtown area. For this, I used the qualitative methodology with ethnographic research approach that, by having a relationship with the educational area, is concerned about the educational processes. For this reason, I emphasize that I adopted some technical procedures of ethnographic research as participant observation and interviews, without losing sight the of the pedagogical dimension of the study. I conducted the research with young in homeless situation, teachers, employees and the teaching staff, both within that school environment, availing myself of the influences of the environment to understand phenomena contextually. This search for schooling and for the institutional space is, before to fight for a right that have been denied to them, to seek for mutual recognition actively participating in social life. The space in question, with its genuinely school character, can operate in the struggle for social recognition of the students. With its ideal standards out of the ones of the network which meets, opposing the heavier side of the balance. The school contributes to the basis for the own recognition of the individual while teaches/educates, provides students the perspective of a social citizen for which the knowledge gained in school, it makes sense.